APAKAH SEKTOR INFRASTRUKTUR DAN KOMODITAS EFISIEN? ANALISIS RETURN ABNORMAL PADA PROGRAM PEN - Rivary Finan Hernawan; Raden Aswin Rahadi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Efficient market is a topic that spurs many interests among financier, due to the significant number of both its proponents and opponents. This paper examines the efficiency of the infrastructure and the commodity sector market in Indonesia by using event study. The PEN (Pemulihan Ekonomi Nasional / National Economic Recovery) event is used as the benchmark event to see whether there is any abnormal return that is generated by the sectors’ market. We calculated the abnormal return and cumulative abnormal return of each of our sample firms in the sector, as well as calculating the average abnormal return and cumulative average abnormal return for each sector. Using the T-test to determine the significancy of the abnormal return, we found that both sectors differ in their efficiency. While we found the infrastructure sector to be efficient, the result of the test on commodity sector instead shows that the sector is inefficient.